DETECTION AND ELIMINATION VIRUS ON POTATO (Solanum tuberosum L.) - Debora Margareth; Ida Ayu Astarini; I Gede Rai Maya Temaja (International Journal of Biosciences and Biotechnology, 2018)
This study aims to determine the symptoms of virus attacks on potato crops, identification of viruses that attack potato plants in Pancasari village, Bali, efectivity of thermotherapy technique to eliminate in vivo potato. The research was taken using purposive sampling technique and complete random program. Virus symptoms were observed on two potato fields. Serological test employed DAS-ELISA with PVX, PVS, PVY and PLRV antiserum. In vivo elimination virus were done by thermoteraphy in 37°C±1°C (4 days), 34°C±1°C (3 days) on 3 weeks and 33°C±1°C (4 days), 30°C±1°C (3 days) on 2 weeks. Results of the study at Pancasari Village Bali shown varied symptoms on potato leaves, such as mottle, mosaic, malformation, leafroll, witchesbroom. Through serological test, had identified viruses were 11.11% PVX, 55.56% PVS, 80% PVY and 11.11% PLRV which were infected farmer’s potato. In vivo thermotherapy was succeed decreasing PVS and PVY level during 2 weeks on 33°C±1°C (4 days) and 30°C±1°C (3 days).